Solutions and limitations of the geomatic survey of an archaeological site in hard to access areas with a latest generation smartphone: the example of the Intihuatana stone in Machu Picchu (Peru) - Baiocchi, Valerio (2022)
Archaeological remains need to be geometrically surveyed and set in absolute reference systems in order to allow a "virtual visit" and to create "digital twins" useful in case of deterioration for proper restoration. Some countries (e.g., Peru) have a vast archaeological heritage whose survey requires optimized procedures that allow high productivity while maintaining high standards of geometric accuracy. A large part of Peru's cultural heritage is located in remote areas, at high altitudes and not easily accessible. For this reason, it is of great interest to study the possible applications of easily transportable instruments. In this study it was verified how the capabilities of the latest smartphones in terms of absolute differential positioning and photogrammetric acquisition can allow the acquisition of a geometrically correct and georeferenced three-dimensional model. The experimentation concerned a new survey of the Intihuatana stones at Machu Picchu and its comparison with a previous survey carried out with a much more complex laser scanning instrumentation. It is important to note that both the photogrammetric survey and the GPS/GNSS survey were carried out with the same smartphone taking full advantage of both features of the same mobile phone. Relative comparison to an existing point cloud provided differences of 2 millimeters in mean with an RMSE of 2 cm. The absolute positioning accuracy compared to a very large-scale cartography appears to be of the order of one metre as was expected mainly due to the high distance of the GPS/GNSS permanent stations